2015
DOI: 10.5535/arm.2015.39.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumatic Compressing Powered Orthosis in Stroke Patients: Preliminary Study

Abstract: ObjectiveTo evaluate the feasibility and effectiveness of a knee-ankle-foot orthosis powered by artificial pneumatic muscles (PKAFO).MethodsTwenty-three hemiplegic patients (age, 59.6±13.7 years) were assessed 19.7±36.6 months after brain lesion. The 10-m walking time was measured as a gait parameter while the individual walked on a treadmill. Walking speed (m/s), step cycle (cycle/s), and step length (m) were also measured on a treadmill with and without PKAFO, and before and after gait training. Clinical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The current modern design of AFOs include articulated devices capable of assisting plantarflexion during stance. Whereas some studies confirmed the benefits of assistive AFOs (Guillebastre et al, 2009 ; Bregman et al, 2011 ; Eddison and Chockalingam, 2013 ; Petrucci et al, 2013 ; Kerkum et al, 2014 ; Kim et al, 2015 ), other studies have asserted a minimal effect of traditional AFOs on global gait kinematics in hemiplegic patients (Yamamoto et al, 1997 ; Mulroy et al, 2010 ). Therefore, taken into consideration the economic cost and the bulkiness of some articulated AFOs, the standard rigid model is still commonly used in rehabilitation practices.…”
Section: Introductionmentioning
confidence: 99%
“…The current modern design of AFOs include articulated devices capable of assisting plantarflexion during stance. Whereas some studies confirmed the benefits of assistive AFOs (Guillebastre et al, 2009 ; Bregman et al, 2011 ; Eddison and Chockalingam, 2013 ; Petrucci et al, 2013 ; Kerkum et al, 2014 ; Kim et al, 2015 ), other studies have asserted a minimal effect of traditional AFOs on global gait kinematics in hemiplegic patients (Yamamoto et al, 1997 ; Mulroy et al, 2010 ). Therefore, taken into consideration the economic cost and the bulkiness of some articulated AFOs, the standard rigid model is still commonly used in rehabilitation practices.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13]. The research object is a person moving with the AFO and spatialtemporal parameters of gait or in combination with foot pressure distribution are analysing [5,[8][9][10]13]. All such works are focused on increasing the efficiency of rehabilitation in clinical field.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, scientists, studying the orthoses and their applicability and reliability, perform tests of two types: static and dynamic. Static test used to find out the maximum load the orthosis could sustain [3][4][5][6][7][8]. Depending on the type of AFO and the existing lesions, and other morphological parameters, the force of support for a person standing can range from 180 N to 900 N. Of course, it depends on the orthosis correct application, the measurement points and way of the usage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current modern design of AFOs includes articulated devices capable of assisting plantar lexion during stance. Whereas some studies con irmed the bene its of assistive AFOs [12,13], other studies demonstrated a minimal effect of traditional AFOs on global gait kinematics in hemiplegic patients [14]. For this reason, taken into consideration the economic cost and the bulkiness of some articulated AFOs, often the clinical attitude is to use standard rigid model in the daily rehabilitation practices.…”
Section: Introductionmentioning
confidence: 99%